STRUKTUR KOMUNITAS IKAN DI SUNGAI TANAP KECAMATAN KEMBAYAN KABUPATEN SANGGAU - Fitri, Dayu Makdalena; Kurniadi, Bambang; Panggabean, Grin Tommy; Amrulloh, Fauzan; Armos, Nikanor Hersal (Akuatik Tropis: Journal of Tropical Aquatic Resource Management, 2024)
The Tanap River is a river in Ngoyok Mandiri Hamlet, Tanap Village, Sanggau District. The Tanap River is used by local villagers for daily needs such as bathing and washing clothes. Apart from that, people usually catch fish for comsumption. The aim of this research is to determine the structure of the fish community in the Tanap River. Samples were collected using trawls, fishing rods, and traps in the June and July 2024. The method used for this research was purpose sampling. Result of research conducted in the Tanap River obtained 16 species of fish consisting of 9 families, namely Clariidae, Bagridae, Belonidae, Nandidae, Osphronemidae, Mastacembelidae, Channidae, Cyprinidae, dan Anabantidae. The highest abundance value of fish species is stove fish (Puntius tetrazona) with a value of 16,71%, while the lowest abundance value of fish (mastacembelus erythrotaenia) with a value of 0,51%, the fish diversity index value ranges from 2,43 "“ 2,53 is categorized as medium diversity. The uniformity index value ranges between 0,90 "“ 0,93 with high criteria, and the dominance index value ranges from 0,09 "“ 0,11 which means dominating other species.  Keywords : Fish community structure, Tanap River